Family Resilience Model: The influence of cultural identity, coping, family strain, socioeconomic status, and community support to the formation of family resilience among Batak Toba ethnic group - Pudjiati, Sri Redatin Retno; Reksodiputro, Sri Hartati Dewi; Purwono, R. Urip (UI Scholars Hub, 2021)
A resilient family is a family that is capable of survival, overcoming difficult challenges, and then grow stronger (Walsh, 2006). Cultural identity is one of the factors that play a role in forming family resilience, because in order to build the understanding and values of family resilience one needs to build it in accordance to local culture. The purpose of this study is to analyze the factors that build family resilience in Indonesian families, especially Batak Toba families. The measurement tool used in this study is Walsh Family Resilience Questionnaire (WFRQ) to measure family resilience (α = .879), The Responses to Stress Questionnaire to measure coping (α = .755), and Family Strains Index to measure strain (α = .763). Another measurement tool is Batak Toba Adat Questionnaire (BAQ) and it is used to measure cultural identity (α = .677), community support, and socioeconomic status. The data is analyzed using Linear Structural Relation (LISREL) through Structural Equation Model (SEM) method. The subject of the study is individuals using Batak Toba surname (N = 295), consisting of 51.2% female and 48.4% male, with age range of 30-65 years old. The percentage of the subject that comes from a big family is 50.85%. The results of the study show that cultural identity, coping, family strain, community support, and socioeconomic status contribute together to build family resilience. The final model produced by this study shows that community support mediated cultural identity and socioeconomic status in building family resilience. Meanwhile, vairables family strain and coping directly affects the shaping of family resilience.